Assessing the Properties of Tree Trunks in Forest Phytocenoses Depending on the Soil and the Climatic Conditions on the Territory of the Taiga Zone of the European North of Russia - Avdeev, Yuri Mikhailovich; Hamitowa, Svetlana Mikhailovna; Kostin, Anton Evgenievich; Lukashevich, Victor Mikhailovich; Lukashevich, Mariya Vasilevna; Kozlov, Andrey Vladimirovich; Uromova, Irina Pavlovna; Trushkova, Marina Aleksandrovna; Davydova, Yuliya Yurevna; Kuzletsov, Vladimir Alekseevich (Journal of pharmaceutical sciences and research, 2018)
Abstract The article presents the data about the effect of the soil and climatic characteristics on the properties of Scots pine trunks in the forest phytocenoses on the territory of the taiga zone of the European North of Russia. Introduction The soil and climatic conditions have significant effect on growth and formation of various plant species, including trees, which has been the subject of many researches in the literature [1-5]. [...]the natural grassland and woody phytocenoses, and plantings of agro-ecosystems in the Northern latitudes get sufficient amount of nutrients from soils of predominantly gley and podzolic types due to their low fertility levels [6-10], while the conditions in Central Russia and in the southern areas, due to the formation of zonal grey soil, black soil and chestnut soil forest bands and intrazonal sod-carbonate soil stains, allow to fully ensure the nutrition conditions for local plant communities due to the high efficient fertility of sod soil cover [11-13]. The results of regression analysis revealed a correlation between the number of branches and the height of the trunk, approximated by the third order parabola equation. [...]defining the diameter at the base of the thickest branches is of practical interest.